2020
DOI: 10.1111/imj.14766
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of oral iron treatment every day and every other day in female patients with iron deficiency anaemia

Abstract: BackgroundIt is known that daily divided doses and high doses of iron increase hepcidin and reduce iron absorption.AimTo compare treatments of iron replacement every other day at low doses, once a day and twice a day in terms of their effectiveness and frequencies of side‐effects.MethodsFor 1 month, Group I received 270 mg ferrous sulphate twice a day (total elemental iron dose: 160 mg/day), Group II received 270 mg ferrous sulphate once a day (total elemental iron dose: 80 mg/day), and Group III received 270 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The results may attributed to the fact that Roxadustat can reduce the hepcidin of the patient's body, thereby increasing the TRF level of the patient's body and helping the patient to stabilize the body's Fe level [ 14 , 15 ]. Rubeor et al revealed that the level of inflammatory factors in patients with CKD and anemia may have a certain relationship with the disease, and over half of the patients are accompanied by active inflammatory response [ 16 , 17 ]. de Lecea have found that inflammatory factors can increase the level of hepcidin in the patient's body, thereby inhibiting the production of EPO in the patient's kidneys, and aggravating the anemia [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results may attributed to the fact that Roxadustat can reduce the hepcidin of the patient's body, thereby increasing the TRF level of the patient's body and helping the patient to stabilize the body's Fe level [ 14 , 15 ]. Rubeor et al revealed that the level of inflammatory factors in patients with CKD and anemia may have a certain relationship with the disease, and over half of the patients are accompanied by active inflammatory response [ 16 , 17 ]. de Lecea have found that inflammatory factors can increase the level of hepcidin in the patient's body, thereby inhibiting the production of EPO in the patient's kidneys, and aggravating the anemia [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…GI side effects (nausea and abdominal pain) were comparable between the two groups (P = 0.57). 10 A randomised controlled study by Düzen Oflas et al 11 included 150 participants and compared AD, CD, and BD dosing of ferrous sulphate over 1 month. Fifty participants received 80 mg of elemental iron twice daily (total daily dose = 160 mg), 50 received 80 mg daily, and the remaining 50 received 80 mg every other day.…”
Section: Evidence To Datementioning
confidence: 99%
“…In summary, two studies reported that AD dosing offered better absorption than CD dosing, 7,10 while another study and metaanalysis concluded that AD dosing may offer comparable efficacy. 11,12 Kaundal et al 9 concluded that, while BD dosing achieved study endpoints more quickly, AD dosing reached the same markers soon after. Of note, evidence to date indicated fewer GI side effects with AD dosing.…”
Section: Application To Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Amon the plethora of so-called superfoods only few of them combine high iron content and anti-inflammatory properties. It is important, indeed, to consider the anti-inflammatory potential of those foods to compensate for possible deleterious effects of high amounts of inorganic iron on the intestinal tract [155][156][157]. Thus, the advantage of administrating balanced supplements releasing iron to the proximal part of the small intestine and, at the same time, provide anti-inflammatory and protective compounds.…”
Section: Superfoods As Nutritional Strategies For Iron Level Replenismentioning
confidence: 99%